Interactions between decision-making and emotion in behavioral-variant frontotemporal dementia and Alzheimer's disease. Issue 6 (1st July 2020) - Manuel, Aurélie L; Roquet, Daniel; Landin-Romero, Ramon; Kumfor, Fiona; Ahmed, Rebekah M; Hodges, John R; Piguet, Olivier
Abstract: Negative and positive emotions are known to shape decision-making toward more or less impulsive responses, respectively. Decision-making and emotion processing are underpinned by shared brain regions including the ventromedial prefrontal cortex (vmPFC) and the amygdala. How these processes interact at the behavioral and brain levels is still unclear. We used a lesion model to address this question. Study participants included individuals diagnosed with behavioral-variant frontotemporal dementia (bvFTD, n  = 18), who typically present deficits in decision-making/emotion processing and atrophy of the vmPFC, individuals with Alzheimer's disease (AD, n  = 12) who present with atrophy in limbic structures and age-matched healthy controls (CTRL, n  = 15). Prior to each choice on the delay discounting task participants were cued with a positive, negative or neutral picture and asked to vividly imagine witnessing the event. As hypothesized, our findings showed that bvFTD patients were more impulsive than AD patients and CTRL and did not show any emotion-related modulation of delay discounting rate. In contrast, AD patients showed increased impulsivity when primed by negative emotion. This increased impulsivity was associated with reduced integrity of bilateral amygdala in AD but not in bvFTD. Altogether, our results indicate that decision-making and emotion interact at the level of the amygdala supporting findings from animal studies.